Type 2 mixed monoclonal IgM and polyclonal IgG cryoglobulinemia can be associated with concurrent renal and intestinal thrombosis: Case report - Sandeep Kumar; Yazan Al-Othman; Sami Zarouk; Ping L. Zhang; Zhenhong Qu (Elsevier, 2022)
Three variants of cryoglobulinemic glomerulopathy are well known, however, the concurrent acute enteritis secondary to a mixed polyclonal cryoglobulin associated thrombotic vasculitis is rarely reported in the literature. We report a case of a 72-year-old man with medical history of hypertension, leukocytoclastic vasculitis, positive serum cryoglobulin, hepatitis C, and membranoproliferative pattern of glomerulonephritis diagnosed 4 years ago. This patient recently presented with abdominal pain for one week. Labs showed worsening renal function, monoclonal IgM-kappa, and positive cryoglobulin in his serum, but negative hepatitis C test. The second renal biopsy showed a membranoproliferative pattern of glomerulopathy with many hyaline thrombi in the glomerular capillary loops. A mixed monoclonal IgM and polyclonal IgG cryoglobulinemic glomerulonephritis (type 2) was diagnosed. His concurrent jejunal biopsy revealed infiltration of neutrophils into glands and submucosal thrombus consistent with ischemic acute jejunitis. The submucosal thrombus of the jejunal biopsy was morphologically similar to the hyaline-thrombi found in glomerular capillary loops. Therefore, we concluded that cryoglobulin associated hyaline thrombi were the most likely etiology for both of his renal disease and acute ischemic jejunitis in this patient. This patient's symptoms are due to simultaneous renal and intestinal thrombosis occurring in cryoglobulinemia. This concurrent thrombosis has not been well described in the literature.